Assessment of Chemical and Physico-Chemical Properties of Cyanobacterial Lipids for Biodiesel Production - Heizir F. De Castro; Marli F. Fiore; Maria E. Silva-Stenico; Patrícia C. M. Da Rós; Caroline S. P. Silva (Marine Drugs, 2013)
Five non-toxin producing cyanobacterial isolates from the genera Synechococcus, Trichormus, Microcystis, Leptolyngbya and Chlorogloea were examined in terms of quantity and quality as lipid feedstock for biofuel production. Under the conditions used in this study, the biomass productivity ranged from 3.7 to 52.7 mg·L−1·day−1 in relation to dry biomass, while the lipid productivity varied between 0.8 and 14.2 mg·L−1·day−1. All cyanobacterial strains evaluated yielded lipids with similar fatty acid composition to those present in the seed oils successfully used for biodiesel synthesis. However, by combining biomass and lipid productivity parameters, the greatest potential was found for Synechococcus sp. PCC7942, M. aeruginosa NPCD-1 and Trichormus sp. CENA77. The chosen lipid samples were further characterized using Fourier Transform Infrared spectroscopy (FTIR), viscosity and thermogravimetry and used as lipid feedstock for biodiesel synthesis by heterogeneous catalysis.